MANAJEMEN STRATEGI PENANGANAN ANAK JALANAN DI KOTA SEMARANG - Indri Dwi Enggar Sari; Endang Larasati Setyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Handling of the street children has a goal to reduce the growth’s number of the street children in the City of Semarang. This research was conducted in Social Department in the City of Semarang by using internal and external environmental organization analysis approach. Internal and external analysis of the organization aims to determine the supporting and inhibiting factors in the management of strategy for handling the street children in the City of Semarang. In the process of handling of the street children in the City of Semarang, the writer uses theory from Bryson about the nine basic steps in strategic planning. The approach that the writer used is descriptive qualitative with the data collection techniques interviews, observation and documentation with the informants who has competence in the field of Social Rehabilitation of Social Tuna and People Trafficking, Social Service Outreach Team (TPD), House of Children Social Protection (RPSA), and Non Governmental Organizations (NGOs). The management of strategy for handling of the street children in the City of Semarang still needs to be improve because there is still a culture of giving and buying from society to street children so that street children continue to feel comfortable to stay in the streets. In searching for the right strategic issues in this study, the authors use SWOT analysis techniques (Strength, Weakness, Opportunities, Threats) and Litmus Test. The results of this study yield four strategic issues and based on Litmus Test, the strategic issue of the management of strategy for handling the street children in the City of Semarang which has the highest score is utilizing the suitability of mission vision accompanied by increased cross-agency cooperation and institutions.